New CDA Orientation Guide - Leading English Education and Resource Network (LEARN) (2023)

Rural Schools, Linguistic Identities, and Official Language Minority Rights : Insights from Rights Holder Parents in Quebec - Pattison-Meek, Joanne; Langevin, Andréanne (2023)
There is considerable scholarly work examining the ways Quebec’s language policies regulate the language of instruction in schools. The current paper contributes to the existing literature by sharing the voices of 21 rights holder parents living in rural areas of Quebec and discussing the ways language of instruction policies influence their school choices and impact their children’s school experiences in rural contexts.
Parallel title: QUESCREN Working Paper no. 9

Bilan annuel : CSC - Plan d'action 2023-2024 - Leading English Education and Resource Network (LEARN) (2023)

Fostering Great Working Relationships in Your School Community - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-06 : Support School Employees - Quebec Federation of Home and School Associations (QFHSA) (2023)
Parallel title : Resolutions Adopted at the 2023 Annual General Meeting